2017
DOI: 10.1002/cncr.31169
|View full text |Cite
|
Sign up to set email alerts
|

Bovine leukemia virus linked to breast cancer but not coinfection with human papillomavirus: Case‐control study of women in Texas

Abstract: The data from the current study supported previous findings of a significant association between BLV DNA in breast tissue and a diagnosis of breast cancer, but did not demonstrate oncogenic strains of HPV associated with breast cancer or the presence of BLV DNA in breast tissue. The authors believe the findings of the current study contribute to overall knowledge regarding a possible causal role for viruses in human breast cancer. Cancer 2018;124:1342-9. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…This problem was remedied by the advent of PCR and DNA sequencing which allowed researchers to detect viral DNA, a more definitive marker of BLV presence. During the past five years several studies on BLV in breast tissues have been performed [8][9][10][11][12][13][14][15]. Their results are summarized in Table 1 below.…”
Section: Summary Of Research On Relationship Of Blv Infection To Breamentioning
confidence: 99%
See 1 more Smart Citation
“…This problem was remedied by the advent of PCR and DNA sequencing which allowed researchers to detect viral DNA, a more definitive marker of BLV presence. During the past five years several studies on BLV in breast tissues have been performed [8][9][10][11][12][13][14][15]. Their results are summarized in Table 1 below.…”
Section: Summary Of Research On Relationship Of Blv Infection To Breamentioning
confidence: 99%
“…The specificity values are all numerical estimates of any similarity being by chance and therefore can be easily compared. The first five studies in Table 1 all used the same primers, which had a close relationship to BLV sequences and an extremely low relationship to the human genome [7][8][9][10][11]. As an additional guarantee of specificity for BLV, these same primers were tested on cell lines infected with other retroviruses closely related to BLV, and also with proven cancer viruses, to make sure there was no positive reaction.…”
Section: Summary Of Research On Relationship Of Blv Infection To Breamentioning
confidence: 99%
“…In the breast cancer patients BLV DNA in mammary is found in 59%, comparing to normal women having 29% with the significant p-value [20,29]. Another study brought even greater presence of BLV in breast cancer patients [30,31]. It worth to note that Gillet and Willems demonstrated absence of BLV DNA in breast cancer patient's DNA.…”
Section: Viral Proteins As Factors Affecting Specific Cancer Pathwaysmentioning
confidence: 92%
“…It worth to note that Gillet and Willems demonstrated absence of BLV DNA in breast cancer patient's DNA. HTLV-1 virus also had been found in the other type of cells in different nonhematological cancers [32]: (i) Endometrial adenocarcinoma in rabbits [33], (ii) Hepatocellular carcinoma (HCC) in patients with chronic HCV infection [34], (iii) Non-small cell lung cancer [35], (iv) Small cell lung cancer [36], (v) HTLV-1 is isolated from immortalized epithelial cells [31], and primary oral keratinocytes [37]. Also, it was shown that HTLV-1 increases risk of bronchioloalveolar carcinoma [38].…”
Section: Viral Proteins As Factors Affecting Specific Cancer Pathwaysmentioning
confidence: 99%
“…Moreover, they assessed HPV presence in these samples. Their conclusion was that there is no association of oncogenic strains of HPV with either breast cancer development or with BLV presence [51].…”
Section: Could Blv Infect Humans?mentioning
confidence: 98%